Analisis Faktor-faktor dalam Penggunaan Bahan Tambahan Pangan di Sekolah Dasar: Analysis of Factors of the Use of Food Additives in the Elementary School - Asyfiradayati, Rezania; Astuti, Dwi; Ambarwati, Ambarwati; Firmansyah, Firmansyah; Kumala, Junisa; Widyasari, Rita Aprilia; Wati, Wiwik Novia; Nindyasari, Jenita Berlian; Mohd Yatim, Siti Rohana (Amerta Nutrition, 2024)
Background: Merchants sell a variety of food for schoolchildren. In an attempt to make the food they offer more enticing and long-lasting, dealers frequently add food additives, sometimes prohibited food additives which is against the law. Predisposing conditions affect the addition of additives to snacks. Objectives: The study aimed to determine the factors that influence the addition of food ingredients not allowed by snack vendors in snacks sold around elementary schools Methods: This study used a survey approach with a cross-sectional design. The 99 traders that made up the study's sample were chosen randomly. The use of food additives was the dependent variable and the independent variables were gender, education, knowledge, age, and length of selling. Test kits were used in laboratories to analyze snack samples sold by traders in order to identify food additives (formalin, borax, Rhodamine B, and Yellow Methanol). Multivariate, bivariate, and univariate analysis were used in the research process. The multiple logistic regression with 95% Confident Interval and chi-square statistical tests were employed in this investigation. Results: The number of snacks checked by test-kit with the result was 21.2% of snacks containing prohibited food additives with a good level of knowledge on the sword as much as 52.5%. The results of the chi-square test statistics for knowledge (p=0.001), age (p=0.010), length of sale (p=0.022) was related to the use of prohibited food additives. The results of multivariate analysis showed that knowledge was the most influential factor in the use of food additives. Conclusions: Traders' knowledge about the use of food additives was the main factor, besides that relate factors were age and length of selling.